2-(6-Hydroxyhexylthio)-5, 8-dimethoxy-1, 4-naphthoquinone Induces Apoptosis through ROS-Mediated MAPK, STAT3, and NF-κB Signalling Pathways in Lung Cancer A549 Cells. (12th August 2020) - Shen, Gui-Nan; Wang, Cheng; Luo, Ying-Hua; Wang, Jia-Ru; Wang, Rui; Xu, Wan-Ting; Zhang, Yi; Zhang, Yu; Zhang, Dong-Jie; Jin, Cheng-Hao
Abstract : Two novel compounds, 2-(2-hydroxyethylthio)-5, 8-dimethoxy-1, 4-naphthoquinone (HEDMNQ) and 2-(6-hydroxyhexylthio)-5, 8-dimethoxy-1, 4-naphthoquinone (HHDMNQ), were synthesized to investigate the kill effects and mechanism of 1, 4-naphthoquinone derivatives in lung cancer cells. The results of the CCK-8 assay showed that HEDMNQ and HHDMNQ had significant cytotoxic effects on A549, NCI-H23, and NCI-H460 NSCLC cells. Flow cytometry and western blot results indicated that HHDMNQ induced A549 cell cycle arrest at the G2/M phase by decreasing the expression levels of cyclin-dependent kinase 1/2 and cyclin B1. Fluorescence microscopy and flow cytometry results indicated that HHDMNQ could induce A549 cell apoptosis, and western blot analysis showed that HHDMNQ induced apoptosis through regulating the mitochondria pathway, as well as the MAPK, STAT3, and NF- κ B signalling pathways. Flow cytometry results showed that intracellular reactive oxygen species (ROS) levels were increased after HHDMNQ treatment, and western blot showed that ROS could modulate the intrinsic pathway and MAPK, STAT3, and NF- κ B signalling pathways. These effects were blocked by the ROS inhibitor N-acetyl-L-cysteine in A549 cells. Our findings suggest that compared with HEDMNQ, HHDMNQ had the stronger ability to inhibit the cell viability of lung cancer cells and induce apoptosis by regulating the ROS-mediated intrinsic pathway and MAPK/STAT3/NF- κ B signalling pathways. Thus, HHDMNQ might be a potential antitumour compound for treating lung cancer.